Faktor-Faktor yang Mempengaruhi Nilai Perusahaan: Perspektif Kebijakan Dividen, Kepemilikan Manajerial, dan Ukuran Perusahaan (Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2023) - Rr.Supantiningrum (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to examine the effect of dividend policy, managerial ownership, and company size on company value. This study was conducted on non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2023, with a population of 64 companies using saturated sampling techniques. The research method uses a quantitative approach through multiple linear regression analysis, with secondary data sourced from the financial statements of companies listed on the Indonesia Stock Exchange. The data analysis process was carried out using SPSS software. The results of the study indicate that dividend policy, managerial ownership, and company size significantly have a positive effect on company value. For further research, it is recommended to use a longitudinal approach to understand how the relationship between dividend policy, managerial ownership, and company size and company value changes over time.